Plastics on the rocks: the invisible but harmful footprint of shoe soles - Cecchi, Philippe (Comptes Rendus. Géoscience, 2023)
Outdoor recreational activities for leisure and for sport training have grown in popularity. Their environmental impacts remain little studied, especially the waste generated by over-frequentation. Our objective was to document how frequentation of a short mountain hiking trail can lead to significant quantities of waste. To this aim, all small objects found along a three-kilometer trail were collected and their origin determined. Polymers were predominant, and were mostly shoe sole fragments. This has never been documented and must be publicized due to the potential harmfulness to terrestrial and riparian ecosystems, and to increase the walkers’ awareness.